Improvements in total mortality and lipid levels after acute myocardial infarction in an English health district (1995–1999). Issue 5 (1st May 2002) - Harrop, J; Donnelly, R; Rowbottom, A; Holt, M; Scott, A R
Abstract : Objectives: To quantify changes in 30 day and one year mortality among patients with acute myocardial infarction in southern Derbyshire (population 560 000) in each of five consecutive years (1995–1999) before the publication of the National Service Framework for coronary heart disease, and to assess the proportion of one year survivors in whom serum lipids were measured and were below target values. Design: All hospital admissions coded on the patient administration system (PAS) as "AMI" (ICD codes I-21, I-22, and I-23) and with a creatine kinase measurement in the pathology database were identified over a five year period (n = 4912). All deaths in the district are automatically notified to the PAS. Total mortality after acute myocardial infarction (30 days and one year) and lipid levels were analysed by year of admission, age group (35–74 years v ≥ 75 years), and sex using unconditional logistic regression analysis. Setting: An acute hospitals trust and pathology laboratory, as sole service providers for a catchment population of 560 000. Results: The number of admissions for acute myocardial infarction was similar in each of the five years (n = 4912, 62% male, 63% < 75 years old). Overall, among patients aged 35–74 years there were 396 deaths (13%) at 30 days and 585 (19%) at one year; mortality was higher in women (1.28-fold at 30 days, p = 0.02) and in subjects aged 75 years or more (3.26-fold at 30 days, p < 0.0001). There was a progressive reduction in 30 day mortality of 9%/year over the five year period (95% confidence interval, 4% to 13%, p = 0.012). The proportion of one year survivors (35–74 years) in whom serum lipids were measured at least once increased from 74% in 1995 to 88% in 1999; of these, 27% of men and 23% of women had a total serum cholesterol of < 5 mmol/l in 1995, increasing to 65% and 74%, respectively, in 1998 and 1999 (p < 0.0001). Conclusions: In the five year period 1995–1999, there was a significant year on year decline in 30 day and one year mortality after admission for acute myocardial infarction, and progressively more patients achieved cholesterol levels below 5 mmol/l. Men were more likely than women to have their lipids measured after myocardial infarction. Mortality at one year was 1.32-fold higher among women than among men.